Developmental Pharmacokinetics and Safety of Ibuprofen and Its Enantiomers in the Conventional Pig as Potential Pediatric Animal Model - Millecam, Joske; van Bergen, Thomas; Schauvliege, Stijn; Antonissen, Gunther; Martens, Ann; Chiers, Koen; Gehring, Ronette; Gasthuys, Elke; Vande Walle, Johan; Croubels, Siska; Devreese, Mathias (Frontiers in Pharmacology, 2019)
Pediatric drug development, especially in disease areas that only affect children, can be stimulated by using juvenile animal models not only for general safety studies, but also to gain knowledge on the pharmacokinetic and pharmacodynamic properties of the drug. Recently, the conventional growing piglet has been suggested as juvenile animal model. However, more studies with different classes of drugs are warranted to make a thorough evaluation whether the juvenile pig might be a suitable preclinical animal model. Ibuprofen is one of the most widely used non-steroidal anti-inflammatory drugs in human. The present study determined the PK parameters, gastro-intestinal and renal safety of 5 mg/kg BW ibuprofen after single intravenous, single oral and multiple oral administration to each time eight pigs (four males, four females) aging 1, 4, 8 weeks and 6–7 months. Oral administration was performed via a gastrostomy button. A jugular catheter was used for intravenous administration and blood sampling. To assess NSAID induced renal toxicity, renal function was evaluated using iohexol and p-aminohippuric acid as markers for glomerular filtration rate and renal plasma flow, respectively. After the trial, necropsy and histology was performed to evaluate macroscopic and microscopic gastro-intestinal as well as renal lesions. Both enantiomers, R-ibuprofen and S-ibuprofen, were determined in plasma using an in-house developed and validated UHPLC-MS/MS method. Pharmacokinetic parameters were estimated using compartmental analysis. Clearance and volume of distribution of total ibuprofen and both enantiomers increased with age as was observed in human. The rate of stereochemical conversion decreased with age. Multiple oral dosing decreased the absolute oral bioavailability and maximum plasma concentration of R-ibuprofen and food consumption did not influence drug absorption. Based on the limited available pediatric literature, the current study might suggest the conventional pig as suitable animal model to evaluate NSAIDs for pediatric use.